Single-cell profiling guided combinatorial immunotherapy for fast-evolving CDK4/6 inhibitor-resistant HER2-positive breast cancer - Qingfei Wang (Nature Portfolio, 2019)
The benefit of combined CDK4/6 and anti-HER2 therapy in breast cancer is limited due to acquired resistance. Here, the authors perform single-cell analysis and show an immature myeloid cell population to infiltrate resistant tumors, and that combined cabozantinib and checkpoint therapy overcome this resistance with a sustained efficacy.